2021
DOI: 10.1155/2021/6620087
|View full text |Cite
|
Sign up to set email alerts
|

Study on Unsteady Cavitation Flow and Pressure Pulsation Characteristics in the Regulating Valve

Abstract: A combined numerical-experiment investigation on the unsteady cavitation flow and pressure fluctuation characteristics in the regulating valves is conducted in this paper. The cavitation flow in the regulating valve is an unsteady and periodic flow which could be divided into fixed and travelling cavitation bubbles. The fixed cavitation bubbles are formed in the gap in the initial stage and then fell off and formed the travelling cavitation bubbles because of the re-entrant jet. The travelling cavitation bubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…To simplify the numerical model, this paper assumes that the flow in the cone valve is axisymmetric and there are no circumferential gradients in the flow. Therefore, the axisymmetric model (Xiumei et al, 2021) is selected for the simulation, as shown in Figure 3. The boundary conditions of the "Inlet" and "Outlet" are pressure-inlet and pressure-outlet, respectively; the "Boundary of valve seat" and "Boundary of spool" are rigid wall; and the "symmetry axis" is the symmetric axis.…”
Section: Methodsmentioning
confidence: 99%
“…To simplify the numerical model, this paper assumes that the flow in the cone valve is axisymmetric and there are no circumferential gradients in the flow. Therefore, the axisymmetric model (Xiumei et al, 2021) is selected for the simulation, as shown in Figure 3. The boundary conditions of the "Inlet" and "Outlet" are pressure-inlet and pressure-outlet, respectively; the "Boundary of valve seat" and "Boundary of spool" are rigid wall; and the "symmetry axis" is the symmetric axis.…”
Section: Methodsmentioning
confidence: 99%